Experiment realization and simulation of new vertical rotating disk of eddy current separator - Nadjib, Kadri; Wafa, Krika; Erkan, Kadir; Bozkort, Ahmet Fevzi; El Islam, Ayad Ahmed Nour; Khelifa, Sabri; Rais, Abdelmajid; Tahar, Rouibah (WYDAWNICTWO SIGMA-NOT SP ZOO, 2024)
The eddy current separation is an efficient and simple technique to recover conducting particles without contact and doesn't need water in the separation process. There are several types of eddy current separators in industry that can be classified according to different characteristics: kind of separates particles, orientation: horizontal and vertical, magnetic field magnitude: high gradient and intensities, and other criteria. The aim of this paper is to concept eddy current separator prototype of rotational vertical disc with a new improved concept of strong permanent magnet distributions of 8 poles. This kind of separator uses spiral or big permanent magnets with few numbers, but our devise is characterized by an important number of strong permanent magnets on the surface of vertical disk to produce an important magnetic field and strong ejection force. The eddy current separator is modeled and simulated with finite element method to show the magnetic flux density near the dynamic separator and to compute the induced current and Lorentz force on two different natures of non-ferrous particles. The experiments separation results by this new prototype help to recovery non-ferrous particles from mixture waste using ejection magnetic force with a rate of 100%. Moreover, the device was developed to sort and purify the non-ferrous particles with maximum separation rate and important ejection distance. The proposed simulation and experiment results can be used to improve several separator parameters.
Keywords: Disk; Eddy currents; Permanent magnet; Separator; Vertical; SMALL NONFERROUS PARTICLES; METALLIC PARTICLES; Engineering